2012
DOI: 10.1002/jwmg.403
|View full text |Cite
|
Sign up to set email alerts
|

Colony connectivity of Pacific Coast double‐crested cormorants based on post‐breeding dispersal from the region's largest colony

Abstract: To reduce conflicts with fish resources, other colonial waterbirds, and damage to habitats, double‐crested cormorants (Phalacrocorax auritus) are currently controlled (lethally and non‐lethally) throughout much of their range. Concerns are growing over the Pacific Coast's largest double‐crested cormorant colony at East Sand Island (ESI), Oregon near the mouth of the Columbia River, where cormorants forage on juvenile salmonids, many of which are listed under the United States Endangered Species Act. Management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However, the tendency for mark–recapture studies to underestimate dispersal distances has been established in previous studies (Koenig, Van Vuren, & Hooge, ; Schneider, ; Yamamura, Kishita, Arakaki, Kawamura, & Sadoyama, ). Additionally, we found a number of telemetry studies that reported mean bird dispersal distances much larger (50–533 km; Aebischer, Nyffeler, & Arlettaz, ; Courtot et al, ; Ferrer, ; Muriel, Morandini, Ferrer, & Balbontín, ; Rahman, Batbayar, Purev‐Ochir, Etheridge, & Dixon, ) than the largest mean distance (of 25. 8 km) estimated by Paradis et al ().…”
Section: Discussionmentioning
confidence: 79%
“…However, the tendency for mark–recapture studies to underestimate dispersal distances has been established in previous studies (Koenig, Van Vuren, & Hooge, ; Schneider, ; Yamamura, Kishita, Arakaki, Kawamura, & Sadoyama, ). Additionally, we found a number of telemetry studies that reported mean bird dispersal distances much larger (50–533 km; Aebischer, Nyffeler, & Arlettaz, ; Courtot et al, ; Ferrer, ; Muriel, Morandini, Ferrer, & Balbontín, ; Rahman, Batbayar, Purev‐Ochir, Etheridge, & Dixon, ) than the largest mean distance (of 25. 8 km) estimated by Paradis et al ().…”
Section: Discussionmentioning
confidence: 79%
“…Fall, winter, and spring surveys have documented flyway-significant aggregations of these species during the non-breeding portion of the annual cycle, as well as other migratory piscivorous species, including Ringbilled Gulls (Larus delawarensis), California Gulls, Herring Gulls (L. argentatus), Black Terns (Childonias niger), Forster's Terns (Sterna forsteri), and Black Skimmers (Shuford et al 2002). The ubiquitous use of the Salton Sea by Caspian Terns from two colonies (> 95% of all tracked individuals) documented in this study is remarkable for a population migrating moderate or long distances (e.g., ≥ 1,500 km) within the Pacific Flyway (Courtot et al 2012).…”
Section: Discussionmentioning
confidence: 59%
“…A majority of Pacific Flyway terns also stopover for a short period during the spring pre-breeding northward migration, while a small minority overwinter there. Other piscivorous waterbirds, including Double-crested Cormorants (Courtot et al 2012) and American White Pelicans (Pelecanus erythrorhynchos), migrating from distant breeding locations have also been documented to use the Salton Sea as a migratory stopover or overwintering location. Fall, winter, and spring surveys have documented flyway-significant aggregations of these species during the non-breeding portion of the annual cycle, as well as other migratory piscivorous species, including Ringbilled Gulls (Larus delawarensis), California Gulls, Herring Gulls (L. argentatus), Black Terns (Childonias niger), Forster's Terns (Sterna forsteri), and Black Skimmers (Shuford et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This study addressed the question of whether cormorants will use artificial colonies, but determining where these colonies should be placed is also important. Cormorants from the East Sand Island colony may prospect for nesting sites hundreds of kilometers from the Columbia River estuary because postbreeding double‐crested cormorants from East Sand Island disperse as far as 530 km from the colony (Courtot et al ). Based on maximum foraging distances of double‐crested cormorants reported by previous studies (Neuman et al , Anderson et al , Coleman et al ), alternative colony sites should be ≥50 km from sites where fish species of special concern are susceptible to cormorant predation.…”
Section: Discussionmentioning
confidence: 99%